Identifikasi Tata Ruang dan Pengenalan Alat-Alat Di Laboratorium Mikrobiologi - Moch. Naufal Ramdhani; Ateng Supriyatna (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
Laboratory is a place to do learning, research, and observation. Practicum is one of the many types of learning methods that exist in schools. The laboratory has the meaning of a room in which practical or research activities are carried out which are equipped with various kinds of equipment such as complete laboratory equipment and infrastructure. Microbiology is one of the materials from Biology lessons, whose scope can be in the form of microbes, fungi or molds, algae, fermentation, viruses, diseases, protozoa, bacteria, microbiology to biotechnology, and the invention of microbiology laboratory techniques. This university also has an Integrated Laboratory as a learning and practice facility in which there are many laboratory rooms according to their respective departments such as biology, physics, chemistry, electrical engineering, informatics, and mathematics laboratories. Then the special tools that are always used in research are Laminar Air Flow, autoclaves, incubators, ovens, refrigerators, and colony counters to count bacterial colonies.